Production Implementation of BAM Music Program on TVRI Riau Kepri - Heriyanto Heriyanto (Jurnal Imiah Teknik Studio, 2022)
A good television program is able to translate the script into pictures and sound (audio visual). In addition to creative elements, in producing television programs including music programs, one must also pay attention to the stages of production implementation/standard operating procedure (SOP). SOP for television program production includes planning, production and post-production stages. The research focuses on the application of SOP/production stages of the Band Anak Muda (BAM) music program at TVRI Riau Kepri. The BAM Music Program raises the potential of bands in Pekanbaru and its surroundings. This study aims to analyze the stages of production of BAM's music program at TVRI Riau Kepri. The analytical method used is qualitative analysis with qualitative data used are questions related to the stages of production. The results of the study find that the production stages of BAM's music program were in accordance with the standard operating procedure, which became the standard for television broadcasting. All stages of production were carried out optimally and thoroughly, evaluations were carried out for improvements in the next episode. Later when Covid-19 has passed, BAM music program can invite audience to be present at the time of production at the studio of TVRI Riau Kepri Station, in order to further build the atmosphere.